2010
DOI: 10.1159/000315362
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Empirical Eating Disorder Phenotypes in a Clinical Female Sample: Results from a Latent Class Analysis

Abstract: Background/Aims: To empirically classify phenotypes of eating disorders (ED) using latent class analysis (LCA), and to validate this classification based on clinical outcomes. Methods: LCA was applied to 968 inpatients. The resultant classes were validated by clinical outcomes including mortality. Results: A 5-class solution showed the best fit. The symptoms of latent class 1 (LC1; 26% of the sample) resembled anorexia nervosa (AN), bingeing-purging (AN-B/P) subtype; those of LC2 (23%) resembled bulimia nervos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 85 publications
4
10
0
Order By: Relevance
“…Overall, empirically derived latent classes from our Hong Kong sample showed substantial correspondence with recognizable lifetime ED phenotypes, including those described in DSM‐5 and identified in previous latent structure models. Our findings are therefore consistent with previous LPA studies in culturally Western and primarily Caucasian samples that have identified classes resembling AN (Bulik et al, ; Dechartres et al, ; Keel et al, ), BN (Bulik et al, ; Pinheiro et al, ; Striegel‐Moore et al, ; Eddy et al, ; Keel et al, ; Sullivan et al, ), and BED (Bulik et al, ; Pinheiro et al, ; Striegel‐Moore et al, ), although our simultaneous application of current and lifetime symptoms as LPA indicators prevents us from evaluating perfect correspondence. Interestingly, the fat‐phobic low‐weight and overweight disordered eating groups are consistent with recent observations that the clinical features of EDs in Hong Kong are becoming increasingly similar to those observed in Western countries (Lee et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, empirically derived latent classes from our Hong Kong sample showed substantial correspondence with recognizable lifetime ED phenotypes, including those described in DSM‐5 and identified in previous latent structure models. Our findings are therefore consistent with previous LPA studies in culturally Western and primarily Caucasian samples that have identified classes resembling AN (Bulik et al, ; Dechartres et al, ; Keel et al, ), BN (Bulik et al, ; Pinheiro et al, ; Striegel‐Moore et al, ; Eddy et al, ; Keel et al, ; Sullivan et al, ), and BED (Bulik et al, ; Pinheiro et al, ; Striegel‐Moore et al, ), although our simultaneous application of current and lifetime symptoms as LPA indicators prevents us from evaluating perfect correspondence. Interestingly, the fat‐phobic low‐weight and overweight disordered eating groups are consistent with recent observations that the clinical features of EDs in Hong Kong are becoming increasingly similar to those observed in Western countries (Lee et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, fewer LPA studies have generated data pertaining to the role of fear of weight gain in AN. While several LPAs have identified subgroups of low to normal weight individuals who exhibit mild to moderate weight concerns (Dechartres et al, 2011;Eddy et al, 2009;Eddy et al, 2010;Keel et al, 2004;Keel et al, 2011;Mitchell et al, 2007;O'Toole et al, 2011), only two have identified a subgroup clearly resembling non-fat-phobic AN, in which shape and weight concerns are essentially absent (Crow et al, 2012;Wildes et al, 2013). For example, in Crow et al (2012), the majority of members in one latent class had a body mass index (BMI) below 19.0 kg/m 2 but did not endorse fear of weight gain.…”
mentioning
confidence: 99%
“…First, this association may be a reflection of illness severity. Lowest illness-related BMI has been reported in several investigations to be a marker of illness severity (Dechartres et al, 2011; Hofman, Landewe-Cleuren, Wojciechowski, & Kruseman, 2009; Mehler, Sabel, Watson, & Andersen, 2008). As such, lowest BMI may be associated with more extreme endorsement of all symptoms – including sensitivity to sensation and avoidance of sensation.…”
Section: Discussionmentioning
confidence: 96%
“…The objective of LCA is to find the smallest number of groups (i.e., latent classes) such that patients in one group are similar to one another but distinct from patients in other groups Reinecke, 2010). This method was primarily developed in psychiatry and related fields (Pickles et al, 1995;Kendler et al, 1998;Breslau et al, 2005;Leoutsakos et al, 2010;Dechartres et al, 2011), and postulates that the associations among a set of observed variables are the result of a common underlying latent class structure. LCA has been used in various medical fields, mainly as a means of identifying homogenous patient groups without relying solely on clinician perceptions (Silverwood et al, 2011).…”
Section: Discussionmentioning
confidence: 99%